Woman's character and advancement in different countries - Voiles, Olive J. (My University, 1897)
Introduction: “Hail, thou that art highly favored, the Lord is with thee: blessed art though of woman.”—Luke 1:28. If we were to travel this wide world over, we would find women in the very lowest degree of intelligence, indeed, we would find those to whom such words as intelligence or civilization would in no way apply. It has been said that the best indication of the progress of civilization in different nations is the condition and treatment of their women. And I think this is very true: if a nation is civilized, the women are treated, at least, as on a level with the men. Respected and shielded by the men, as they should be and not used as slaves, brutes almost. And when they are not treated well, it surely may be said that the nation is not civilized. I think woman was created for a companion, helper, and guide for her husband, and not for a slave. What would a nation be without a home, and what is home without a woman. “Who creates a home creates a potent spirit, which, in turn, doth fashion him that fashioned.” We may truly say the home not only fashions the fashioner but all that dwell therein. Place woman at the head of the home and better nations would result.
Citation: Voiles, Olive J. Woman's character and advancement in different countries. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Womens studies; Character; Advancement; Theses; Manuscripts (documents)